7 secrets to break the chains of panic attacks / A breakthrough guide for resolving panic attacks - Alexandra Pentaraki; Brain Matters Institute (2019)
Understanding anxiety and panic attacks, The link between hyperventilation sydrome and panic attacks, Understanding and changing the anatomy of a panic attack, Mood changes and panic attacks, Being human and compassionate with yourself, Diet and substance abuse: Their relationship with anxiety and panic attacks, Affirmative work and healing maps: Affirmations and healing maps for panic attacks